ENT Function in a 14-Days Guinness Scuba Dive - Revelli, L.; D’Alatri, L.; Scorpecci, A.; D’Amore, A.; De Corso, E.; Lombardi, C. P.; Fetoni, A. R. (International Journal of Sports Medicine, 2012)
Scuba diving is known to affect the rhino-pharyngo-tubaric district (RPT unit). The aim of the study was to document function modifications of the RPT unit in 6 Italian divers (3 men and 3 women) who lived for 14 days consecutively at a depth of 8–10 m, breathing air (21% oxygen) at a pressure ranging between 1.8 and 2 ATA. RPT and inner ear assessment were carried out before the dive (TIME 0) and 24 h (TIME 1) after resurfacing, in order to investigate diving-related RPT and inner ear alterations. Physical examination after resurfacing revealed: fungal external otitis, otoscopic findings consistent with middle ear barotraumas and rhinosinusitis. Rhinomanometry showed a remarkable increase in inspiratory nasal flow and a substantial decrease in nasal resistance. No epithelial cell disruption was retrieved comparing pre and post resurfacing samples. Post-diving tubaric dysfunction was found. Pure tone audiometry revealed a bilateral 40 dB HL hearing loss at 4 kHz in 1 diver. Relevant PTA functions did not seem to be affected by the experiment, no remarkable changes were found at the Sensory Organisation Test and at the Motor Control Test. The 14-day underwater period had a positive effect on nasal flows and resistances.
Keywords: hyperbarism; saturation diving; prolonged diving; scuba dive; ENT injury; barotrauma